Leveraging Genetic Data to Elucidate the Relationship Between COVID‐19 and Ischemic Stroke - Verena Zuber (Wiley, 2021)
Background The relationship between COVID‐19 and ischemic stroke is poorly understood due to potential unmeasured confounding and reverse causation. We aimed to leverage genetic data to triangulate reported associations. Methods and Results Analyses primarily focused on critical COVID‐19, defined as hospitalization with COVID‐19 requiring respiratory support or resulting in death. Cross‐trait linkage disequilibrium score regression was used to estimate genetic correlations of critical COVID‐19 with ischemic stroke, other related cardiovascular outcomes, and risk factors common to both COVID‐19 and cardiovascular disease (body mass index, smoking and chronic inflammation, estimated using C‐reactive protein). Mendelian randomization analysis was performed to investigate whether liability to critical COVID‐19 was associated with increased risk of any cardiovascular outcome for which genetic correlation was identified. There was evidence of genetic correlation between critical COVID‐19 and ischemic stroke (rg=0.29, false discovery rate [FDR]=0.012), body mass index (rg=0.21, FDR=0.00002), and C‐reactive protein (rg=0.20, FDR=0.00035), but no other trait investigated. In Mendelian randomization, liability to critical COVID‐19 was associated with increased risk of ischemic stroke (odds ratio [OR] per logOR increase in genetically predicted critical COVID‐19 liability 1.03, 95% CI 1.00–1.06, P‐value=0.03). Similar estimates were obtained for ischemic stroke subtypes. Consistent estimates were also obtained when performing statistical sensitivity analyses more robust to the inclusion of pleiotropic variants, including multivariable Mendelian randomization analyses adjusting for potential genetic confounding through body mass index, smoking, and chronic inflammation. There was no evidence to suggest that genetic liability to ischemic stroke increased the risk of critical COVID‐19. Conclusions These data support that liability to critical COVID‐19 is associated with an increased risk of ischemic stroke. The host response predisposing to severe COVID‐19 is likely to increase the risk of ischemic stroke, independent of other potentially mitigating risk factors.